2020
DOI: 10.3390/ijms21072369
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effects of Silymarin on Benzo[a]pyrene-Induced Hepatotoxicity

Abstract: Benzo[a]pyrene (B[a]P), a polycyclic aromatic hydrocarbon, is a group 1 carcinogen that introduces mutagenic DNA adducts into the genome. In this study, we investigated the molecular mechanisms underlying the involvement of silymarin in the reduction of DNA adduct formation by B[a]P-7,8-dihydrodiol-9,10-epoxide (BPDE), induced by B[a]P. B[a]P exhibited toxicity in HepG2 cells, whereas co-treatment of the cells with B[a]P and silymarin reduced the formation of BPDE-DNA adducts, thereby increasing cell viability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 68 publications
(84 reference statements)
2
16
0
Order By: Relevance
“…Silymarin, a phytocomplex extracted from the medicinal plant Silybum marianum (“milk thistle”), is widely known for its hepatoprotective functions [ 140 ]. In addition, they have a protective effect against injuries to the brain [ 141 ], heart [ 142 ], and kidneys [ 143 ].…”
Section: Resultsmentioning
confidence: 99%
“…Silymarin, a phytocomplex extracted from the medicinal plant Silybum marianum (“milk thistle”), is widely known for its hepatoprotective functions [ 140 ]. In addition, they have a protective effect against injuries to the brain [ 141 ], heart [ 142 ], and kidneys [ 143 ].…”
Section: Resultsmentioning
confidence: 99%
“…In gene knockout models, AhR knockout resulted in increased BPDE-DNA adduct formation compared with the wild type [ 46 ], and NRF2 knockout resulted in enhanced oxidative damage compared with the wild type [ 47 ]. Our previous study on the attenuation of B[a]P cytotoxicity by silymarin revealed that NRF2 knockdown increases BPDE-DNA adduct formation [ 48 ]. Therefore, we hypothesized that (1) quercetin and isorhamnetin increase the expression level of AhR and NRF2, or (2) quercetin and isorhamnetin increase the gene regulatory activity of AhR and NRF2.…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability assay was performed to evaluate the cytotoxicities of B[a]P and curcumin (Sigma-Aldrich Chemical, St. Louis, MO, USA) on HepG2 cells. The concentration (10 µM) of B[a]P was selected based on the evidence reported in our previous study which showed cytotoxicity of the B[a]P occurring in a dose-dependent manner on HepG2 cells [ 8 ]. HepG2 cells were seeded at a density of 1 × 10 4 cells/well in 96-well plates containing MEM with B[a]P (10 µM) or curcumin (0, 1, 5, 10, 20, or 40 µM) and cultured for 48 h. The cells were then incubated with EZ-CYTOX reagent (DOGEN, Seoul, Korea) for an additional 2 h. Cell absorbance at 450 nm was measured using a microplate reader (Tecan, Männedorf, Switzerland), and the cell viability with or without the treatment of B[a]P or curcumin was assessed.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have focused on natural bioactive compounds that are derived from functional foods and attenuate chemical-induced toxicities [ 2 , 7 , 8 ]. Benzo[a]pyrene (B[a]P) is widely known as a chemical carcinogen of polycyclic aromatic hydrocarbon, listed as a group-1 carcinogen by the International Agency for Research on Cancer (IARC) [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%